1993
DOI: 10.1590/s0004-282x1993000200022
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamic tumor associated with atypical forms of anorexia nervosa and diencephalic syndrome

Abstract: We report the case of a 10-year-old girl with a mature teratoma in the hypothalamic region. The patient presented a 2-month history of anorexia, psychic disturbances and a 37% loss of body weight. These symptoms had led initially to a diagnosis of major depression and atypical anorexia nervosa. She also presented some signs and symptoms of diencephalic syndrome. This case illustrates the importance of considering a slow-growing mass as a rare but real possibility in the differential diagnosis of anorexia nervo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…[6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] With one exception these were primary tumours. In addition to abnormal eating behaviour, symptoms commonly included diabetes insipidus, visual impairment, and unprovoked vomiting.…”
Section: Hypothalamic Lesionsmentioning
confidence: 99%
See 1 more Smart Citation
“…[6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] With one exception these were primary tumours. In addition to abnormal eating behaviour, symptoms commonly included diabetes insipidus, visual impairment, and unprovoked vomiting.…”
Section: Hypothalamic Lesionsmentioning
confidence: 99%
“…Twelve cases (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15) were classified as atypical anorexia with unintentional weight loss and, in seven, unprovoked vomiting. Although typical psychopathology was not reported, lack of concern over emaciation was noted in three, depressed mood in five, and obsessive compulsive symptomatology in one case (8). In three (4, 5, and 6) there was suggestive evidence of causal association in that anorexia remitted after surgical or radiation treatment.…”
Section: Tablementioning
confidence: 99%
“…The hypothalamus, particularly a region known as the paraventricular nucleus, is highly implicated in the regulation of feeding. Thus, endocrine disturbances associated with the hypothalamic‐pituitary‐adrenal (HPA) axis could easily be mistaken for an ED .…”
Section: Resultsmentioning
confidence: 99%
“…In fact, it has previously been reported that patients can experience a weight gain during psychotherapy even though the anorexia was caused by a hypothalamic tumor. 9 The patient presented by Rohrer et al 7 had some typical symptoms of anorexia (fear of fatness and disturbed body image) and her laboratory analysis revealed panhypopituitarism. In the cases by Winston et al 6 and Sokol et al, 10 the patients had normal laboratory results, so both situations may present.…”
Section: Discussionmentioning
confidence: 99%